Polytriazole membranes with ultrathin tunable selective layer for crude oil fractionation - Chisca, Stefan; Musteata, Valentina-Elena; Zhang, Wen; Vasylevskyi, Serhii; Falca, Gheorghe; Abou-Hamad, Edy; Emwas, Abdul-Hamid; Altunkaya, Mustafa; Nunes, Suzana P. (Science (American Association for the Advancement of Science), 2022)
The design of materials and their manufacture into membranes that can handle industrial conditions and separate complex nonaqueous mixtures are challenging. We report a versatile strategy to fabricate polytriazole membranes with 10-nanometer-thin selective layers containing subnanometer channels for the separation of hydrocarbons. The process involves the use of the classical nonsolvent-induced phase separation method and thermal cross-linking. The membrane selectivity can be tuned to the lower end of the typical nanofiltration range (200 to 1000 gram mole −1 ). The polytriazole membrane can enrich up to 80 to 95% of the hydrocarbon content with less than 10 carbon atoms (140 gram mole −1 ). These membranes preferentially separate paraffin over aromatic components, making them suitable for integration in hybrid distillation systems for crude oil fractionation. Organic and aprotic solvents will typically destroy polymer separation membranes, thus making it difficult to separate organics by this route. Chisca et al . synthesized polytriazole membranes through film casting and non-solvent-induced phase separation, followed by a simple thermal treatment step to induce chemical cross-linking (see the Perspective by Seo and Koh). This converted the polymer into an asymmetric membrane with an ~10-nm selective layer showing excellent solvent permeability and selectivity. The membranes can enhance the concentration of hydrocarbons with fewer than 10 carbons and were also used for the fractionation of crude oil. —MSL Cross-linked polytriazole polymeric nanofiltration membranes can fractionate crude oil.